Variables Related to the Transition of Youth from School to Work - Taylor, Maurice C.; Thibault, Carol J.; Boss, Marvin W.; Bédard, René; Evans, Karen (Canadian Journal of Counselling and Psychotherapy, 2011)
The purpose of the study was to determine the reliability and validity of a British measure of attitude toward training for new technology, economic locus of control, self-efficacy, and self-estrangement for a Canadian adolescent population. In addition, the relationship between educational settings and beliefs and attitudes of 255 young Canadians soon to enter the work force was examined. The results from the Canadian data were comparable to results from the United Kingdom. Significant differences were obtained for educational settings on the variable of attitude toward training for new technology. Males had significantly more positive attitudes than females toward training for new technology.